The Benefits of Multilingualism to the Personal and Professional Development of Residents of the US - Kroll, Judith F.; Dussias, Paola E. (Foreign language annals, 2017)
In the past two decades, new research on multilingualism has changed our understanding of the consequences of learning and using two or more languages for cognition, for the brain, and for success and well‐being across the entire lifespan. Far from the stereotype that exposure to multiple languages in infancy complicates language and cognitive development, the new findings suggest that individuals benefit from that exposure, with greater openness to other languages and to new learning itself. At the other end of the lifespan, in old age, the active use of two or more languages appears to provide protection against cognitive decline. That protection is seen in healthy aging and most dramatically in compensating for the symptoms of pathology in those who develop dementia or are recovering from stroke. In this article we briefly review the most exciting of these new research developments and consider their implications.